Morphology, Structure, and Ontogeny of Trichomes of the Grape Genus (Vitis, Vitaceae) - Ma, Zhi-Yao; Wen, Jun; Ickert-Bond, Stefanie M.; Chen, Long-Qing; Liu, Xiu-Qun (Frontiers in Plant Science, 2016)
Trichomes are widely distributed on surfaces of different organs in the grape genus Vitis and are of taxonomic utility. To explore the morphology, structure and ontogeny of Vitis trichomes, we investigated the diversity and distribution of trichomes in 34 species of Vitis. Two main types of trichomes in Vitis are documented: non-glandular and glandular. Within non-glandular trichomes, ribbon and simple trichomes are found on different vegetative plant organs. The morphology and ontogeny of these types of trichomes are further examined with light microscopy and scanning electron microscopy. The ultrastructure of the glandular trichomes is explored with transmission electron microscopy. The ribbon trichomes are twisted, greatly elongated and unicellular, and this trichome type may be a morphological synapomorphy of Vitis and its closest tropical relative Ampelocissus and Pterisanthes in Vitaceae. The simple trichomes are documented in most species sampled in the genus. The glandular trichomes are multicellular, non-vascularized and composed of both epidermis and subjacent layers. We show that prickles occurring along the stems and petioles of Vitis davidii are modified glandular trichomes. In our observation, the glandular trichomes of V. romanetii can secret mucilage and send out volatile substance so that many insects are often glued to glands. Transmission electron microscopy indicates that metabolic products accumulate in vacuoles, the cytoplasm and intercellular spaces. We infer that glandular trichomes and young prickles are involved in the secretion of these metabolic products and the intercellular spaces may be the places of temporary storage of these secretions.